Characterization of nesting effects on compression processes for plain woven fabrics in composites manufacturing. (October 2017) - Yang, Xujing; Wang, Yanke; Mo, Fuhao; Wei, Kai; Duan, Shuyong
Nesting and compression processes of plain woven fabrics are the most important features in the composites manufacture of fiber-reinforced composite components, while their relationships are still not reported. Here, in this work, we clearly reveal nesting and compression characteristics of typical fabrics through systematical compression experiments. We present the theoretical expression of the nesting effects on the initial thickness h and experimentally demonstrate its effectiveness. We find that nesting decreases the h and the minimum h appears in the maximum nesting condition. Meanwhile, we experimentally demonstrate that for plain woven fabrics, nesting has relationships with the thickness in compression t, while it has no effects on the thickness deformation Δ in the whole compression processes. Thus, we reveal the relationships between the nesting and h, t, Δ in the compression processes. Moreover, the applicability of these results for other types of fiber is also illustrated by comprehensive analysis. These obtained results provide the references for thickness evolution rules, volume fraction, and molding process of the fiber-reinforced composite components.